Annealing effects on resistive switching of IGZO-based CBRAM devices. (October 2020) - Gan, Kai-Jhih; Liu, Po-Tsun; Ruan, Dun-Bao; Chiu, Yu-Chuan; Sze, Simon M.
Abstract: In this study, the impact of post-oxide deposition annealing on performance of IGZO-based conductive-bridging random access memory (CBRAM) is reported. It is found that besides the distinct reduction in resistive switching parameters of SET/RESET voltages, their dispersions, and the resistance ratio of high-resistance state to low-resistance state can be improved after N2 annealing. The annealing effects on enhancing of the resistive switching properties are investigated by x-ray photoelectron spectra. It can be considered that the formation of the filament is better controlled by the increase of oxygen vacancies in the switching layer, which is the main reason for the improvement of resistive switching characteristics. Highlights: The IGZO-based conductive-bridging random access memory (CBRAM) was fabricated. The high resistance ratio (>10 5 ) and good switching uniformity were obtained. The annealing effect on IGZO-based CBRAM was investigated. The IGZO-based CBRAM has a great potential for the future memory applications.